Association of MC4R codon 42 polymorphism with obese/diabetic ethnic Kashmiri population - Dar, Rubiya; Rasool, Shabhat; Zargar, Ab Hamid; Jan, Tariq R; Andrabi, Khurshid I (Asian Journal of Medical and Biological Research, 2015)
Our objective was to study the sequence variations of melanocortin 4 receptor (MC4R) gene in obese/diabetic populations of the Kashmir region and workout association of such variations (if any) with the disease phenotype. No such study has ever been taken up in the Jammu and Kashmir State, despite the existence of a significant population of obese/diabetic patients. A total of 420 samples were taken in the present study. Among them 200 were obese and 220 were normal. The samples were divided into three groups i.e., normal (220), obese with non diabetics (150) and obese with diabetics (50). Allele frequencies were tested for HardyWeinberg disequilibrium. The genotype and allele frequencies were evaluated using the ?2 tests or the Fisher exact tests. A novel heterozygous variation (Glu42Lys) was observed in all groups at a frequency of 10% in obese with non diabetics, 26% in obese with diabetics and 1.81% in healthy controls (BMI ? 23 kg/m2) which was significantly (p<0.05) higher in both obese or obese with diabetes groups. G to A substituting glutamic acid with lysine appeared to associate with both diabetes and obesity significantly (p< 0.05). Insilico predictions show that substitutions likely have an impact on structure and functional properties of protein making it imperative to understand their functional consequences in relation with diabetes and obesity. These results indicate that this novel genotype may have a possible bearing in the genesis of obesity or diabetes in Kashmiri population. Asian J. Med. Biol. Res. June 2015, 1(2): 149-157